Intercultural sensitivity and linguistic adaptation among Indonesian students in Cairo: A narrative inquiry - Afanin Rushafah; Ulil Fitriyah (JEELS (Journal of English Education and Linguistics Studies), 2026)
While a growing body of research has acknowledged the importance of Intercultural Sensitivity for international students, studies focusing on linguistic adaptation in this context remain limited. This study explores the experiences of Indonesian students in Cairo in adapting their linguistic practices through the adjustment of various linguistic resources in a multilingual context. By using a narrative inquiry approach, the data were collected through written open-ended questions and analyzed using reflexive thematic analysis. The conceptual framework of the Intercultural Sensitivity dimensions by Chen and Starosta (2000) and the Communication Accommodation Theory (CAT) framework developed by Giles (1973, 1991) are employed to examine students’ linguistic adjustment in intercultural encounters. The results showed that students’ level of intercultural sensitivity vary and are affected by their educational background and experience in Arabic and English language acquisition. Students who demonstrated more intercultural sensitivity tended to be more open to local culture, more confident when interacting with local communities, and more flexible in adjusting their linguistic practices. This flexibility is reflected in their language choices, communication strategies, and the forms of linguistic adaptation used in intercultural communication.